A survey of distributed denial-of-service attack, prevention, and mitigation techniques. (December 2017) - Mahjabin, Tasnuva; Xiao, Yang; Sun, Guang; Jiang, Wangdong
Distributed denial-of-service is one kind of the most highlighted and most important attacks of today's cyberworld. With simple but extremely powerful attack mechanisms, it introduces an immense threat to current Internet community. In this article, we present a comprehensive survey of distributed denial-of-service attack, prevention, and mitigation techniques. We provide a systematic analysis of this type of attacks including motivations and evolution, analysis of different attacks so far, protection techniques and mitigation techniques, and possible limitations and challenges of existing research. Finally, some important research directions are outlined which require more attentions in near future to ensure successful defense against distributed denial-of-service attacks.